Working Across Contexts: Practical Considerations of Doing Indigenist/Anti-Colonial Research. (June 2017) - Hart, Michael A.; Straka, Silvia; Rowe, Gladys
Although Indigenous scholars have been documenting Indigenous research methodologies, little has been written on the practical considerations of doing research across Indigenous/Settler contexts. As a small social work research team (two Cree researchers and one Settler) exploring Indigenous aging, our work crossed several contexts: academic and community, social locations within the team, and epistemes. Centering the research on an Indigenist, anti-colonial framework allowed us to highlight and correct for colonial power dynamics throughout the project. By enacting Indigenism together, we found that Indigenous and Settler researchers can create a space of deep learning and knowledge co-creation with communities. However, this work was challenging, risky, and at times difficult. Learning to navigate some of these complexities required ongoing attention to our relational accountabilities. We detail lessons learned from each of our perspectives, concluding with implications, community obligations, and directions for future research.